PENERAPAN PEMBELAJARAN MEDIA AUDIO-VISUAL UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR PADA MATA PELAJARAN BIOLOGI DI KELAS VIII A SMP GKST IMANUEL PALU - Bambang, Lestari (JSTT, 2015)
AbstractThis research was class action research, with the research subject of 28 students. Method used in this research was descriptive method with data collection using instruments; questionaires, study outcomes test and observation checklist. This research aimed to increas students motivation and study outcome through the implementation of Audio-visual Media teaching in Grade VIIIA of SMP GKST Imanuel Palu. The research result showed thatÂ students study motivation before treatment was 39,9% which was categorised low, and after the treatment 81,75% which categorised high. Whereas the students study outcome from the research result showed that there were 10 students completed in cycle I, and there were 27 students in cycle II. The classical absorption in cycle I was 62% and in cycle II was 86%. The classical learning mastery in cycle I was 36%, while in cycle II was 96%. The observation of teachers activity obtained in cycle I was 63,5% in average which categorised as good, the students activity was 70,45% categorised as good. The observation result of teachers activity in cycle II was 91,6% which very good, students activity was 93,18%Â categorised verry good. Based on the result above therefore, it can be concluded that the Implementation of Audio-Visual Media Teaching could increase the students motivation and study outcome in the human motion system lesson at Grade VIII A of SMP GKST Imanuel Palu.Â